Glicerina bruta como suplemento energético para vacas leiteiras em pastejo de azevém - Fraga, Denize da Rosa (2016)
This thesis was developed with the objective of evaluating the effect of supplementation with 10% crude glycerin in the total dry matter (DM) of the diet for lactating cattle in a annual ryegrass (Lolium multiflorum) pasture production system on the metabolic profile, milk composition and production. The experiment was conducted at the Regional Rural Development Institute in Augusto Pestana, RS, Brazil, with 18 Holstein cattle, in a block design (according to lactation days) in a simple cross-over procedure, during three periods of 14 days. The diets were composed of annual ryegrass grazing and supplementation with corn silage and concentrate, with or without addition of 10% crude glycerin based on total dry matter. Samples of diet, urine, milk and blood were collected and evaluated. It were evaluated too milk production and leftover food in the trough. The data were submitted to analysis of variance and the treatment effect compared by the T test through the SAS statistical program. Values of P<0.05 were considered significant and tendency were considered when P<0.10. It was verified that the inclusion of 10% of crude glycerin in diet DM of lactating cows reduces the elimination of urea through milk and increases blood glucose levels, and does not have a deleterious effect on milk production and cows’ feed consumption. The addition of 10% DM of glycerin to the diet hasn’t effect on milk production and composition of Holstein cows in different lactation periods with different levels of protein in the diet. It was concluded that the inclusion of 10% crude glycerin in diet DM of lactating cows on annual ryegrass pasture reduces the level of milk nitrogen urea. This could be due to the decrease in urea blood levels by the increase of nutritional efficiency, provided by glycerin energy supply, for its energy and potential contribution in increasing blood glucose levels, without interfering in the productive performance and composition of the milk.